Animal objects? - Acknowledging the moral limits of property law - Trigg, R (2023)
At present, animals are categorised as objects in law, whereas humans are categorised as subjects. Animals have or they are capable of having human property rights accrue in them and, as such, they are treated only as being instrumentally valuable. This is in contrast to the inherent value recognised in the human context. The law has conflated a human/animal dualism with the subject/object distinction in property law. The aim of this thesis is to consider the relationship between subjecthood and objecthood through a study of the status of animals. In doing so, I challenge the longstanding and pervasive assumption in traditional property theory and practice that animals are properly regarded as property objects. This thesis brings together the core fundamental aspects of the concept of property, highlighting that one of the fundamental features is that it contains a moral limitation. At present, this moral limitation prevents humans from being treated as property objects, doing so by recognising their subjecthood. Thus, I posit that the moral limit of property is the concept of subjecthood. I conduct a study of the attribution of subjecthood to humans and extract four key elements, which I term the “irreducible core”, that forms the basis of that recognition. I move on to examining whether the attribution of subjecthood only to humans, and thus the present moral limit of property, is morally consistent and justifiable. In concluding that it is not, I propose a new theory of subjecthood or personhood that draws from existing legal principles – centring the importance of the irreducible core but conceiving of it and applying it non-anthropocentrically to be inclusive of all humans and other animals. In proposing this new theory of personhood, I argue that the moral limitation of property should be reimagined – recasting animals as subjects and removing them from the property paradigm as objects.